The concept of plea bargaining in criminal proceedings (Journal of actual problems of jurisprudence, 2019)
The article is considered on a concept of institution of plea bargaining in criminal proceedings of Kazakhstan.Some scientists consider the position on the concept of the legal phenomenon. Issues of proceduralregulations of the institution addressed in the draft Code of Criminal Procedure as amended. In the project,this institution is called a procedural agreement. By analyzing this concept the author give suggestions forimprovement of the term.Keywords: transaction; agreement; guilt; defendant.